ERROR ANALYSIS OF INDONESIAN STUDENTS IN LEARNING TIME ASPECT "? ZHE" AT NANCHANG UNIVERSITY IN CHINA - Septevany, Elvira; Dandan, Liu; Marsuki, Ria Rizki (Lire Journal (Journal of Linguistics and Literature), 2020)
For foreign students, the Mandarin time aspect “?zhe” is a common and relatively difficult grammar point to grasp. The research method used is a quantitative method and a qualitative descriptive method to describe, identify the types of mistakes made by Indonesian learners in the learning time aspect “?zhe”. The data collection technique used is purposive sampling, i.e. Mandarin language learners at the University of Nanchang, China, which had received writing, grammar and structure, and syntax courses. The purpose of this technique is to obtain relevant data in order to solve the problem of learning Mandarin, especially regarding the time aspect “? zhe”. The results of the relevant questionnaire show that Indonesian students lack basic knowledge of time aspects and they did not understand or forget the rules of time aspect. So, they use Indonesian grammar to answer the Mandarin time aspect “? zhe” questionnaire. This is indicated by the results of the questionnaire given, there are 3 forms of performance errors above 50%, i.e. misuse error has 65%, a misordering error has 60%, an added error has 55% and there is 1 form error below 50% namely omission error, has 45%. The Conclusions of time aspect Mandarin "? zhe" is a form of Mandarin grammar that is often used. This time aspect "? zhe" has several rules in matching with other words. To understand this, Indonesian students need to learn step by step and perseverance in study and practice, so they can understand the uses of time aspect "? zhe".